2017
DOI: 10.1634/theoncologist.2016-0246
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Venous Thromboembolism in Ambulatory Cancer Patients: The ONKOTEV Study

Abstract: Background. The efficacy of risk model scores to predict venous thromboembolism (VTE) in ambulatory cancer patients is under investigation, aiming to stratify on an individual risk basis the subset of the cancer population that could mostly benefit from primary thromboprophylaxis. Materials and Methods. We prospectively assessed 843 patients with active cancers, collecting clinical and laboratory data. We screened all the patients with a duplex ultrasound (B-mode imaging and Doppler waveform analysis) of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 36 publications
4
97
0
8
Order By: Relevance
“…Khorana score was the first validated risk assessment model (RAM) for identifying VTE high-risk patients receiving chemotherapy. After this publication, different RAM have been published and some of them have been validated (Table 3) [24][25][26][27][28][29][30][31][32]. Other RAM addressed to specific tumors such as THROLY [33] or testicular germ cell tumors [34].…”
Section: Prophylaxis Of Vte In Ambulatory Cancer Patients During Systmentioning
confidence: 99%
See 1 more Smart Citation
“…Khorana score was the first validated risk assessment model (RAM) for identifying VTE high-risk patients receiving chemotherapy. After this publication, different RAM have been published and some of them have been validated (Table 3) [24][25][26][27][28][29][30][31][32]. Other RAM addressed to specific tumors such as THROLY [33] or testicular germ cell tumors [34].…”
Section: Prophylaxis Of Vte In Ambulatory Cancer Patients During Systmentioning
confidence: 99%
“…Compared to LMWH or UFH, fondaparinux was not statistically different in all endpoints including mortality, recurrence VTE, and bleeding. In the second meta-analysis [53], a subgroup analysis of cancer patients Vienna CATS score [25] PROTECHT score [26] CONKO score [27] Oncothromb-Tic Onco score extended [28,29] Compass-CAT score [30] a Onkotev score [31] Pabinger et al [32] Tumor vascular/ lymphatic compression reported a significant reduction in mortality with LMWH compared to UFH (OR 0.53, 95% CI 0.33-0.85; p = 0.009).…”
Section: Initial Treatment Of Vte In Cancer Patients (5-10 Days)mentioning
confidence: 99%
“…of high-risk patients were diagnosed with VTE within months of initiating chemotherapy (25,38). We utilized a prespecified VTE-independent adjudication committee that included a central radiology review of all radiographic studies indicative of a thrombotic event.…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%
“…The ONKOTEV score [89] was developed using a large multicenter prospective cohort of 843 cancers patients. Overall, 73 (8.6%) VTE events occurred during a median follow-up of 8.3 months.…”
Section: Risk Assessment Models (Ram) For Prediction Of Vte In Patienmentioning
confidence: 99%